2013
DOI: 10.1111/ctr.12171
|View full text |Cite
|
Sign up to set email alerts
|

De novo malignancy post–liver transplantation: a single center, population controlled study

Abstract: Background With the growing numbers of liver transplant recipients, it is increasingly important to understand the risks of de novo malignancy after liver transplantation. Aim To characterize the incidence of de novo malignancy after liver transplantation compared to a control non-transplant population. Methods We studied 534 Indiana state residents undergoing liver transplantation at our center between 1997 and 2004, followed through August 2010 The incidence and predictors of malignancy were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…[1][2][3] In addition, posttransplant immunosuppression has been shown to accelerate carcinogenesis. 4 Serial abdominal crosssectional imaging (CSI) is regularly performed in pre-LT patients for operative planning and hepatocellular carcinoma screening, increasing the likelihood of incidental findings, including intraductal papillary mucinous neoplasms (IPMNs) of the pancreas.…”
mentioning
confidence: 99%
“…[1][2][3] In addition, posttransplant immunosuppression has been shown to accelerate carcinogenesis. 4 Serial abdominal crosssectional imaging (CSI) is regularly performed in pre-LT patients for operative planning and hepatocellular carcinoma screening, increasing the likelihood of incidental findings, including intraductal papillary mucinous neoplasms (IPMNs) of the pancreas.…”
mentioning
confidence: 99%
“…In a previous study comprising 118 patients transplanted for ALD between 1982 and 1993 at the Medical University of Vienna, patients were found to be compliant regarding post‐LT clinical investigations and appointments for psychological counseling . Including any consumption of alcohol, 16.2% of our patients experienced an alcohol relapse during the observation period.…”
Section: Discussionmentioning
confidence: 72%
“…These results were further supported by a Spanish case–control study, though patients with and without cancer were not matched for gender and age . In addition, a recent investigation reported that patient survival was diminished only in the subset of patients with DNM excluding nonmelanoma skin cancer, compared with patients without cancer …”
Section: Discussionmentioning
confidence: 82%
“…Although DNM has been reported in some investigations as a major cause of late mortality after LT, few studies have evaluated the effects of cancer on survival comparing LT recipients who developed DNMs with corresponding LT recipients who did not . Moreover, none of these investigations has assessed cancer outcomes starting from the date of cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%